The Blind Giant Is Dancing. - Sewell, Stephen (Current Theatre Ser., 2016)
Brutality in the workplace, rage in the streets, seething in the home. The vulnerability of political parties when they've forgotten why they're there. The intellectual torpor of modern Australia. How power corrupts. The Blind Giant is Dancing is an angry and tender depiction of an idealist, Allen Fitzgerald, who becomes so embroiled in a party power struggle that he loses sight of what's at stake. When it premiered in 1983, The Blind Giant is Dancing felt like a sharp slap in the face. Now, in an age of ICAC, union credit cards, speculative housing bubbles, a pulverised working class and vapid.